The unique autosampler of split-loop design (direct injection) for Russian market in Skorohod HPLC series - N. A. Novozhilova; A. V. Sevko (Разработка и регистрация лекарственных средств)
Skorohod HPLC series is manufactured by family enterprise Sevko & Co on its own production facilities in Pushkinsky district of Moscow region. This series occupies the unique position on Russian market of analytical equipment not only because of the maximum localization of all the components in one production enterprise and independence of the whole tool on the scarce Western analogue details. Technical solutions, implemented in Skorohod, let it possible to put this HPLC on the same level with high-end Western HPLC manufacturers, which left Russian market. Some of technical solutions are exclusive by world standards as well. In this article we will discuss the autosampler from Skorohod series that utilizes direct injection (split-loop), commonly used between the largest producers of HPLC, but so far not available for Russian users.